THE EFFECT OF CUSTOMER SATISFACTION ON REPEAT PURCHASE INTENTION (CASE STUDY: DISHWASHING SOAP IN SUB-DISTRICT POIGAR) - Mawitjere, Praisethy M.; Tulung, Joy E.; Wangke, Shinta J. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
Currently, there is so much research discussing the customer satisfaction related to viral products on repurchase intention. Only limited research has examined the common products, which is taken here as a regular product purchase that the customers frequently purchase.Â This study aims to analyze which customer satisfaction factors namely price, product quality, or efficiency (accessibility of the product), greater affect the repeat purchase intention of dishwashing soap products in sub-district Poigar. Dishwashing soap is taken here as a common product or regular purchase where frequently purchased and low-involvement in the decision-making process. The data were generated by distributed questionnaires and interviews to 100 respondents using purposive sampling with the following requirement: the married women aged 19-60 years old in Poigar. The data was analyzed using the Multiple Linear Regression method. The result of all factors simultaneously positively affects repeat purchase intention. Product quality is the greater factor that affects the repeat purchase intention. Meanwhile, price is a sensitive factor. Therefore, the company and local parties have to set reasonable prices among society, especially those with middle to lower economies.Â Keywords: customer satisfaction, price, product quality, efficiency, common product, repeat purchase intention.